Misconceptions about gyroscopic stabilization - Müller, Patric; Sack, Achim; Pöschel, Thorsten (American Journal of Physics, 2020)
A spinning gyroscope resists small torques in directions perpendicular to its axis, that is, the angular orientation of a body rigidly attached to a gyroscope is stable against rotation around certain axes. Since the angular orientation of a body is described by three angles (e.g., Euler angles), one might conclude that it is possible to stabilize the orientation of an object against rotation using a combination of three gyroscopes spinning around non-collinear axes. We perform experiments under conditions of weightlessness to demonstrate that systems of coupled gyroscopes cannot arrest the angular orientation of free-floating objects, in contradiction to a widespread myth about gyroscopic stabilization, based on the above arguments. (C) 2020 American Association of Physics Teachers.
CRIS-Team WoS Importer:2020-06-26